ANALYSIS OF COMPANY RISK IN FINANCIAL ACCOUNTING REPORTING - Yuliana Yuliana; Nelcie Mussa; Ika Ismiyar; Effendi Tjahjadi; Agus Munandar (SEAN Institute, 2023)
The purpose of this study was conducted to draw a conclusion related to risk management for every activity carried out by the organization in previous research, especially risks that can affect financial reports based on the results of a summary of the conclusions. The literature review used in this study is to determine company activities related to risk management, financial performance and reporting, good corporate governance, human resources and information technology. The research method is based on journals and observations of literature reviews that have something to do with research problems. The study technique uses qualitative methods based on existing journals and articles. The results of the study synthesized that all the variables in previous research were connected to risk management which consisted of how to mitigate, evaluate, and analyze each risk that could affect the performance of an organization.